1998
DOI: 10.1029/98gl00300
|View full text |Cite
|
Sign up to set email alerts
|

Ozone depletion in and below the Arctic Vortex for 1997

Abstract: Abstract. The winter 1996/97 was quite unusual with late vortex formation and polar stratospheric cloud (PSC) development and subsequent record low temperatures in March. Ozone depletion in the Arctic vortex is determined using ozonesondes. The diabatic cooling is calculated with PV-theta mapped ozone mixing ratios and the large ozone depletions, especially at the center of the vortex where most PSC existence was predicted, enhances the diabatic cooling by up to 80%. The average vortex chemical ozone depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 15 publications
3
82
0
Order By: Relevance
“…In the absence of mixing, correlations between a long-lived tracer and ozone provide a quantitative measure of chemical O 3 change [Müller et al, 2001[Müller et al, , 2005. TRAC has been successfully used to quantify chemical O 3 loss for the past decade of Arctic [Tilmes et al, 2004] Harris et al [2002] showed general agreement of TRAC-derived O 3 loss with O 3 loss derived from Lagrangian trajectory [Manney et al, 1995], vortex average [Knudsen et al, 1998], SAOZ [Goutail et al, 1999] and Match [von der Gathen et al, 1995] calculations.…”
Section: Data and Analysismentioning
confidence: 86%
“…In the absence of mixing, correlations between a long-lived tracer and ozone provide a quantitative measure of chemical O 3 change [Müller et al, 2001[Müller et al, , 2005. TRAC has been successfully used to quantify chemical O 3 loss for the past decade of Arctic [Tilmes et al, 2004] Harris et al [2002] showed general agreement of TRAC-derived O 3 loss with O 3 loss derived from Lagrangian trajectory [Manney et al, 1995], vortex average [Knudsen et al, 1998], SAOZ [Goutail et al, 1999] and Match [von der Gathen et al, 1995] calculations.…”
Section: Data and Analysismentioning
confidence: 86%
“…The effect of export of chemically activated air out of the vortex is also small, as seen from the following arguments: The exported air will only deplete the air outside the vortex for, say, 10 days. However, the air inside the vortex stays activated for about 60 days on average in the two winters studied here [Rex et al., 1999; Knudsen et al, 1998b]. Since the exported air constitutes less than about 50% of the vortex area, the exported air only has a depletion potential of less than about 1/12 of that of the vortex air.…”
Section: Mixingmentioning
confidence: 99%
“…Although there are certain assumptions involved in this method, it does give a correct depletion in the winter 1999/2000 (Lait et al, 2002;. It has been shown that mixing ideally should be taken into account at the bottom of the vortex and below (Knudsen et al, 1998) and in some years even above (Grooß and Müller, 2002). Rex et al (2004) found a high correlation between mean PSC volume and mean end-of-winter column ozone depletion.…”
Section: Correlation Between Psc Area and Ozone Depletionmentioning
confidence: 99%